Love is no laughing matter = No hay burlas con el amor - Calderón de la Barca, Pedro, 1600-1681 (Hispanic classics. Golden-Age drama., 1986)
Although Calderon's comedy has received rather less attention than the other genres in which he excelled, it is widely acknowledged that his comic plays are inrivalled among his contemporaries in terms of plot structure and technical expertise; they also explore contemporary issues to an extent which has not been appreciated. Love is no Laughing Matter is one of the best, in which the dramatist casts a sardonic eye on male chauvinism, women's education and social snobbery. This is the first complete text of the play to be published since 1650. Spanish text with facing-page translation.